Impact of parenting parents on the incidence of violence in dating on adolescents - Sakinah, Luthfiatus (Berita Kedokteran Masyarakat, 2021)
Objective: Parenting plays a role dating violence occurence, this has become a research topic that is being widely researched. To understand this research, the purpose of this study is to analyze the impact of parenting style with dating violence occurence in adolescents. Content: Family is the most important socialization agent in a person’s life, because family is the first sphere between people and society. Parenting style is an important role in shaping and developing oneself as a person and character. Types of parenting styles for parents are authoritarian, democratic, permissive, and indifferent or negligent. The better the parenting style given by the parents, the better the child’s behavior. Teens will see and learn by recording and doing actions that have been accepted as well as getting parenting styles. Dating violence is a form of aggressive behavior from acts of violence against adolescents. Dating violence occurs more often in women than men, this is due to gender inequality. Dating violence can occur physically, psychologically, sexually and economically. The factors of the occurrence of violence in dating can occur by psychological factors as well as non-psychological and sociological factors. The impact of violence in dating is that the victim will feel anxious, cause feelings of fear to leave or escape from the control of the victim’s actions or routines so that it reduces the spirit of life, low self-esteem, does not have the courage to set up relationships, productivity or achievement and can cause trauma.